Changes in health outcomes as a function of abstinence and reduction in illicit psychoactive drug use: a prospective study in primary care. (September 2015) - Park, Tae Woo; Cheng, Debbie M.; Lloyd‐Travaglini, Christine A.; Bernstein, Judith; Palfai, Tibor P.; Saitz, Richard
Abstract Aims To test (1) whether abstinence and reduction in illicit psychoactive drug use were associated with changes in health outcomes in primary care patients and (2) whether these associations varied by drug type. Design Secondary analysis of data from a randomized controlled trial that tested a brief intervention for drug use in primary care patients (589 enrolled, 574 completed a 6‐month assessment). Analyses were conducted overall and stratified by the most commonly self‐identified main drugs (marijuana, cocaine and opioids). Setting and Participants Patients who screened positive for illicit drug use at an urban primary care clinic in Boston, Massachusetts, USA. Measurements Differences in past‐month main drug use at baseline and 6‐month outcome were categorized as continued or increased use, decreased use without abstinence and abstinence. Primary outcomes were 6‐month changes in drug use consequences [Short Inventory of Problems scores (range 0–45)], depressive symptoms and health‐related quality of life (HRQol). Findings Abstinence was associated with a greater decrease in adverse drug use consequences than continued or increased use among the full sample and cocaine and opioids subgroups (adjusted means, full sample: –8.11 versus –0.05, P < 0.001; cocaine: –13.33 versus +1.09, P < 0.001, opioids; –16.84 versus –2.10, P < 0.001). Differences were not significant between those who decreased use compared with those who continued or increased use. There were no significant associations between drug use and depressive symptoms or HRQol. Neither abstinence nor decreased use was associated significantly with consequences in the marijuana subgroup. Conclusions Among primary care patients in the United States who use illicit psychoactive drugs, abstinence but not reduction in use without abstinence appears to be associated with decreased adverse drug use consequences.